2020
DOI: 10.1111/jcal.12475
|View full text |Cite
|
Sign up to set email alerts
|

Student engagement with mobile‐based assessment systems: A survival analysis

Abstract: Research on mobile-based assessment systems is still an emerging topic in the mobile learning field. Current research has demonstrated that the use of mobile-based assessment systems seems to have a positive impact on students' learning outcomes and motivation. The paper identifies some factors that influence student engagement with mobile-based formative assessment in a language learning course. Survival analysis of the interaction of N = 86 students from eight English as a Foreign Language (EFL) courses over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 59 publications
4
22
0
Order By: Relevance
“…While these platforms can be used for taking online exams, they also serve to enhance the innovative learning platforms through hosting brainstorming sessions and holding interactive lectures. A good example of that is mentioned by Akour et al [126] and Bacca-Acosta et al [127], which in turn helps in enhancing students' retention and satisfaction [128][129][130]. System quality and content quality are found to be prerequisite drivers that affect students' acceptance and adoption of mobile examination and learning applications, as declared by Liu et al [131].…”
Section: Discussionmentioning
confidence: 95%
“…While these platforms can be used for taking online exams, they also serve to enhance the innovative learning platforms through hosting brainstorming sessions and holding interactive lectures. A good example of that is mentioned by Akour et al [126] and Bacca-Acosta et al [127], which in turn helps in enhancing students' retention and satisfaction [128][129][130]. System quality and content quality are found to be prerequisite drivers that affect students' acceptance and adoption of mobile examination and learning applications, as declared by Liu et al [131].…”
Section: Discussionmentioning
confidence: 95%
“…Hanafi et al [47] also investigated the use of m-LMSs for religious training in universities in Indonesia by application of the ADDIE model (analysis, design, development, implementation, and development). Researchers from Colombia [48] evaluated mobile assessment systems using 86 students who were learning English as a second language. They concluded that between the 25th min and 50th min the probability of disengagement is high.…”
Section: Recent Research and M-lmsmentioning
confidence: 99%
“…However, survival analysis can also be applied to other contexts. For instance, recent studies used survival analysis to evaluate students’ engagement within online learning environments [8] , [9] , [10] , [11] , [12] , [13] , [14] . In this study, we applied this approach to evaluate students’ engagement – and, conversely, dropout rates – over time for different time periods as observed for the online learning environment Bettermarks .…”
Section: Introductionmentioning
confidence: 99%